The impact of pianist-controlled engaged mass on piano keystroke dynamics - Somma Antonio; Roudet Jeanne; Fabre Benoît (Acta Acustica)
The conventional methods used to measure and model the dynamics of a piano keystroke typically involve applying force at the key front using mechanical excitation. However, the influence of the actuator mass on the resulting motion and force profile has never been addressed. Conversely, within the realm of piano technique, mechanical excitation occurs through engagement with parts of the pianist’s body, whose mass can vary significantly. Pianists claim to have the ability to adjust the mass they engage at will. We propose a new approach that integrates the pianists’ bodily presence into the mechanical system under examination. By doing so, we aim to reformulate the control parameters associated with piano keystrokes, as typically discussed in scientific literature. This approach yields a simplified model of a pressed keystroke that incorporates the presence of an actuator mass. Through minimally invasive experiments, we observe the relationship between tone volume and driving force, considering levels of inertia comparable to those engaged by pianists through their bodies, with excitation starting at the surface of the key. The results are consistent with our proposed model, highlighting the antagonistic role of total inertia in piano tone production. This approach broadens our understanding of pianists’ control strategies and sheds light on its complex interplay with musical needs in piano performance.